STRATEGI MANAJEMEN PENDIDIKAN ANAK USIA DINI DALAM MENINGKATKAN KUALITAS LAYANAN PEMBELAJARAN - Ari Widhyastuti; Novan ardy wiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the educational management strategies implemented at RA Diponegoro 2 Penaruban, Bukateja, Purbalingga Regency in improving the quality of early childhood learning services. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the management strategies at RA Diponegoro 2 involve participatory and needs-based planning, child-centered active learning implementation, and regular and constructive supervision. Furthermore, parental involvement and teacher capacity building are key components of the strategy to enhance the quality of education. The impact of these strategies is evident in the significant improvement of children's development, the quality of teacher-child interactions, and the increased participation of parents in educational activities. This study concludes that structured, collaborative, and development-oriented management can effectively improve the quality of learning services in early childhood education institutions. Keywords: Educational Management, Early Childhood, Strategy, Learning Services, PAUD